2007
DOI: 10.5194/nhess-7-591-2007
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ground geoelectric activity between three regions of different level of seismicity

Abstract: Abstract. In this work, we present a statistical study of geoelectric time series from three Mexican regions with recognized different levels of seismicity. This study is made by means of both the Higuchi's method and the detrended fluctuation analysis for the detection of fractal behavior. With these methods we present scatter plots corresponding to scaling exponents for short and large lags arisen from crossover points in the geoelectric data. Through these scatter plots we observe a reasonable segregation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Previous studies have reported changes in the correlation dynamics observed prior to this earthquake [27,[36][37][38][39]. However, the possible existence of seismic precursors associated with this event has not been deeply explored.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have reported changes in the correlation dynamics observed prior to this earthquake [27,[36][37][38][39]. However, the possible existence of seismic precursors associated with this event has not been deeply explored.…”
Section: Introductionmentioning
confidence: 97%
“…We have measured the ground electrical potential (the self-potential) at several sites along the Mexican coast, near the Middle American trench, which is the border between the Cocos and the American tectonic plates. In some previous articles we have reported more detailed descriptions of that region and some studies of possible precursory electric phenomena associated with several earthquakes of magnitude larger than six [26][27][28]. Recent studies focused on fractal and non-linear properties of physical and biological times series have revealed that this organization is strongly related to a complex interaction of multiple components and mechanisms across multiple scales.…”
Section: Introductionmentioning
confidence: 97%
“…We have measured the ground electrical potential (the selfpotential) in several sites along the Mexican coast, near the Middle American trench, which is the border between the Cocos and the American tectonic plates. In some previous articles we have reported more detailed descriptions of that region and some studies of possible precursory electric phenomena associated to several earthquake of magnitude larger than six (Muñoz-Diosdado et al, 2004;Ramírez-Rojas et al, 2007;Flores-Márquez et al, 2007). Recent studies focused on fractal and non linear properties of physical and biological times series have revealed that this organization is strongly related to a complex interaction of multiple components and mechanims across multiple scales.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, our study is related to an Ms=7.4 earthquake ocurred on 14 September 1995. Previous studies by our group have reported changes in the correlation dynamics observed prior to this earthquake (Ramírez-Rojas et al, 2007. We use the sample entropy algorithm to evaluate the level of regularity of geolectric time series across multiple time scales.…”
Section: Introductionmentioning
confidence: 99%
“…We have measured the ground electrical potential (the self-potential) in several sites along the Mexican coast, near the Middle American trench, which is the border between the Cocos and the American tectonic plates. In some previous articles we have reported more detailed descriptions of that region and some studies of possible precursory electric phenomena associated to several earthquakes of magnitude larger than six (Flores-Márquez et al, 2007;Muñoz Diosdado et al, 2004;Ramírez-Rojas et al, 2007). Recent studies focused on fractal and non linear properties of physical and biological times series have revealed that this organization is strongly related to a complex interaction of multiple components and mechanism across multiple scales.…”
Section: Introductionmentioning
confidence: 98%